E-policy : how to develop computer, e-mail and internet guidelines to protect your company and its ass - Overly, Michael R. (American Management Association New YorkUS, 1999)
Addresses steps which businesses can take to protect themselves against e-mail related problems, with the primary focus on developing written computer and e-mail policies. Includes topics such as: privacy rights of employees; discrimination and harassment issues; copyright infringement; spamming; and, the protection of attorney-client communication. Provides examples of policies, selected laws, and regulations.